Automatic Measurement Method of Yarn Dyed Woven Fabric Density via Wavelet Transform Fusion Technique (Journal of Fiber Bioengineering and Informatics, 2016)
The yarn density is always considered as the fundamental structural parameter used for the qualityevaluation of woven fabrics. Conventional yarn density is measured by one-side image analysis. In thispaper, a novel density measurement method is developed for yarn dyed woven fabrics based on dual-sidefusion technique. Firstly, both face-side and back-side image of woven fabric are acquired via a lab-useddual-side imaging system. Secondly, the affine transform is used for dual-side image alignment. Then, thecolor images of woven fabrics are transferred from RGB to CIE-Lab color space, the intensity informationof image extracted from L component is used for the texture fusion and analysis. Subsequently, the dual-side image is merged by the self-developed Wavelet transform fusion method. Finally, the fast Fouriertransform is utilized to measure yarn density of the fused image, the yarn alignment image could bereconstructed using inverse fast Fourier transform. Our experimental results show that the accuracy ofdensity measurement by using proposed method is close to 99.44% compared with traditional methodand the robustness of this new proposed method is better than that of conventional analysis methods.